Choosing Alternatives to Single-Use Plastics: Factors Influencing Youths' Consumption Intentions in Hanoi - Ha, Nguyen Viet; Phuong Chi, Nguyen; Huong, Pham Bao Thien; My, Nguyen Ha; Nam, Nguyen Hoang (VNU Journal of Science: Policy and Management Studies, 2025)
Single-use plastic products, despite their convenience and familiarity, have raised increasing concerns due to their detrimental long-term impacts on the environment and human health. Consequently, alternatives such as rice straws and paper bags have been increasingly developed. However, the crucial challenge lies in changing consumer habits and promoting the adoption of these alternatives. This study expands upon the Theory of Planned Behavior (TPB) to examine the primary factors influencing consumer behavior: Attitude, Subjective Norms, Perceived Behavioral Control toward Consumption Intenton. Primary data from a survey of young people in Hanoi is analyzed using Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), and Structural Equation Modeling (SEM). The findings reveal that subjective norms and perceived behavioral control significantly impact consumers' intention regarding the adoption of alternatives. This highlights the importance of enhancing the availability and accessibility of alternatives, as well as utilizing social influence to guide the community towards sustainable consumption practices.